2000
DOI: 10.1161/01.str.31.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Female Gonadal Steroids in Reproductively Senescent Female Rats

Abstract: Background and Purpose-Young adult female rats sustain smaller infarcts after experimental stroke than age-matched males. This sex difference in ischemic brain injury in young animals disappears after surgical ovariectomy and can be restored by estrogen replacement. We sought to determine whether ischemic brain injury continues to be smaller in middle-aged, reproductively senescent female rats compared with age-matched males and to test the effect of ovarian steroids on brain injury after experimental stroke i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
4
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(264 citation statements)
references
References 62 publications
11
248
4
1
Order By: Relevance
“…4,33,34 Other studies have either not investigated survival or the reported numbers of deaths are small, thereby preventing detailed analysis. Importantly, only death post treatment should be included, and earlier culling, e.g., because of inadequate occlusion (as determined using laser Doppler), does not amount to attrition bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,33,34 Other studies have either not investigated survival or the reported numbers of deaths are small, thereby preventing detailed analysis. Importantly, only death post treatment should be included, and earlier culling, e.g., because of inadequate occlusion (as determined using laser Doppler), does not amount to attrition bias.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were excluded, mostly because they did not have data on total lesion volume or vital status, e.g., one study only had data on blood volume collected. 4 Data Set Characteristics Data set characteristics are reported in Tables 1 and 2. The data sets used compared the effect of exogenously administered progesterone versus no progesterone, or vehicle, on lesion volume after acute focal cerebral ischemia, as well as data sets involved in the analysis of death and progesterone plasma concentration.…”
Section: Study Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…This advantage is abolished in ovariectomized animals, due to the loss of endogenous female sex hormones (Simpkins et al , 1997 ;Alkayed et al , 1998Alkayed et al , , 2000Hawk et al , 1998 ;Liao et al , 2001 ;Gibson et al , 2005 ;Park et al , 2006 ;Dra č a, 2009 ;Selvamani and Sohrabji , 2010 ), and the consequences of cerebral ischemia in aged animals are more severe than in young animals (Davis et al , 1995 ;Alkayed et al , 1998 ).…”
Section: Neuroprotectionmentioning
confidence: 99%